N-Propyl-N-Methylpyrrolidinium Difluoro(oxalato)borate as a Novel Electrolyte for High-Voltage Supercapacitor - Zhang, Weili; Zhang, Fuming; Zhang, Peng; Liang, Shuo; Shi, Zhiqiang (Frontiers in Chemistry, 2019)
Development of high voltage electrolyte is one of the effective ways to improve the performance of supercapacitor. The new ionic liquid N-propyl-N-methylpyrrolidinium difluoro(oxalato)borate (Py13DFOB) was designed and mixed with propylene carbonate (PC) as electrolyte for supercapacitor. The operating voltage of the new electrolyte system has been proven to be up to 3.0 V by a series of electrochemical techniques. Surprisingly, the new salt exhibits nearly symmetric capacitance contribution in the positive and negative electrodes, leading to a high capacitance value of 130 F g-1. The energy and power density of EDLCs using Py13DFOB in the PC electrolyte reach 39.06 Wh kg-1 (100 mA g-1) and 8.03 kW kg-1 (5000 mA g-1), respectively, at the working voltage of 3.0 V, significantly exceeding the performance of commercial electrolyte tetraethylammonium tetrafluoroborate (TEABF4). The results indicate that Py13DFOB can be a promising electrolyte salt for supercapacitor.